1987
DOI: 10.1038/bjc.1987.123
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione localisation in benign and malignant human breast lesions

Abstract: Summary Reduced glutathione (GSH) has been demonstrated in benign and malignant human breast lesions using a newly.developed histofluorescence technique. GSH was present in every lesion and in each case was localised to the epithelium. A semi-quantitative assessment revealed a moderate amount of GSH in normal epithelium and fibroadenoma and a high level in apocrine metaplasia, epitheliosis and intraduct carcinoma. Invasive ductal carcinoma contained a variable amount of GSH. Correlation between fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Subsequent studies have confirmed that the reduc ing environment produced by this tripeptide plays a pro tective role against oxidative stress brought about by free radicals, reactive oxygen compounds and toxic com pounds of endogenous and exogenous origin [3]. Further, the fact that the amount of GSH has been found to vary greatly in a number of pathophysiological conditions involving cellular defence [5] has aroused interest in the field of tumour research.…”
Section: Introductionmentioning
confidence: 90%
“…Subsequent studies have confirmed that the reduc ing environment produced by this tripeptide plays a pro tective role against oxidative stress brought about by free radicals, reactive oxygen compounds and toxic com pounds of endogenous and exogenous origin [3]. Further, the fact that the amount of GSH has been found to vary greatly in a number of pathophysiological conditions involving cellular defence [5] has aroused interest in the field of tumour research.…”
Section: Introductionmentioning
confidence: 90%
“…Most studies treated isolated tissue with protein denaturing acids to remove this transpeptidase and slow oxidation. Two studies using histological preparations of tissue samples likely inactivated degradative enzymes during tissue fixation (Murray, Burke and Ewen 1987; Woolston et al 2011). …”
Section: Breast Cancersmentioning
confidence: 99%
“…Depletion of GSH levels in the cells could promote tumor development in different animal species [9]. Supporting this suggestion, depletion of GSH level and inhibition of GST activity were found to reduce the covalent binding of the ultimate metabolites of both aflatoxin B 1 and benzo[a]pyrene, with DNA [10], and decreasing of hepatocarcinogenesis caused by these compounds was correlated with low the level of DNA adducts [10].…”
Section: Introductionmentioning
confidence: 98%